Avaliação do potencial de formigas (Hymenoptera: formicidae) como vetores mecânicos de bactérias do gêneroSstaphylococcus no ambiente hospitalar. - Silva, Eutália Elizabeth Novaes Ferreira da (2009)
In a hospital environment, these bacteria can be spread by insects such as ants, which are characterized by high adaptability to the urban environment. Staphylococcus is a leading cause of hospital infection. In Europe, Latin America, USA and Canada, the group of coagulase negative staphylococci (CoNS) is the second leading cause of these infections, according to SENTRY (antimicrobial surveillance program- EUA). In this study, we investigated the potential of ants (Hymenoptera: Formicidae) as vehicle mechanics of Staphylococcus bacteria in a public hospital, in Natal-RN. The ants were collected, day and night, from June 2007 to may 2008, in the following sectors: hospitals, laundry, kitchen, blood bank. The ants were identified according to the identification key of Bolton, 1997. For the analysis of staphylococci, the ants were incubated in broth Tryptic Soy Broth (TSB) for 24 hours at 35 º C and then incubated on Mannitol Salt Agar. The typical colonies of staphylococci incubated for 24 hours at 35 ° C in Tryptic Soy Agar for the characterization tests (Gram stain, catalase, susceptibility to bacitracin and free coagulase). The identification of CoNS was performed through biochemical tests: susceptibility to novobiocin, growth under anaerobic conditions, presence of urease, the ornithine decarboxylation and acid production from the sugars mannose, maltose, trehalose, mannitol and xylose. The antimicrobial susceptibility examined by disk-diffusion technique. The technique of Polymerase Chain Reaction was used to confirm the presence of mecA gene and the ability to produce biofilm was verified by testing in vitro using polystyrene inert surface, in samples of resistant staphylococci. Among 440 ants, 85 (19.1%) were carrying coagulase-negative staphylococci (CoNS) of the species Staphylococcus saprophyticus (17), Staphylococcus epidermidis (15), Staphylococcus xylosus (13), Staphylococcus hominis hominis (10), Staphylococcus lugdunensis (10), Staphylococcus warneri (6), Staphylococcus cohnii urealyticum (5), Staphylococcus haemolyticus (3), Staphylococcus simulans (3), Staphylococcus cohnii cohnii (2), and Staphylococcus capitis (1). No Staphylococcus aureus was found. Among the isolates, 30.58% showed resistance to erythromycin. Two samples of CoNS (2.35%), obtained from the ant Tapinoma melanocephalum collected in the post-surgical female ward, S. Hominis hominis and S. lugdunensis harbored the mecA gene and were resistant to multiple antibiotics, and the specie S. hominis hominis even showed to be a biofilm producer. This study proves that ants act as carriers of multidrug-resistant coagulase-negative Staphylococci and biofilm producers and points to the risk of the spreading of pathogenic microorganisms by this insect in the hospital environment